Assessment of Landfill Odorous Gas Effect on Surrounding Environment - Si-liang Shen; Bin-hai Wu; Hui Xu; Zhen-ying Zhang (Advances in Civil Engineering)
Landfill odorous gas emission has been a serious environmental problem, especially for the residents or passersby on the road near the landfill. In this paper, in situ monitoring and the numerical CALPUFF model were adopted to analyze the odor nuisance problem caused by municipal solid waste (MSW) degradation in a large landfill. The static chamber technique was used to measure the odorous gas emission rate on the working area, temporary cover area, and final cover area of the landfill during Dec. 2016 and Apr. 2018. The results showed that the emission rate of H2S on the working area varied from 0.003 mg/m2/min to 0.98 mg/m2/min, and it was positively correlated with the ambient temperature. The emission of H2S varied between 0.125 kg/h and 1.09 kg/h on the working area, and it varied between 9.2 × 10−6 kg/h and 6.8 × 10−4 kg/h on the temporary cover when considering the impact of the holes in a high-density polyethylene (HDPE) membrane, and it was negligible on the final cover. The contribution rates of H2S emission in the whole landfill were 90.79%∼98.59% and 0.0008%∼0.52% for the working area and the temporary cover area, respectively. The numerical simulation showed that wind velocity and gas emission rates were the critical factors that affect odor dispersion. To limit the H2S-influenced area within the landfill site, proper engineering measures should be taken to ensure the H2S emission rate of lower than 15% of its original value.